2017
DOI: 10.1021/acs.energyfuels.7b02581
|View full text |Cite
|
Sign up to set email alerts
|

Speciation Characteristics and Mobility of Trace Elements Across Ultralow Emission Air Pollution Control Devices

Abstract: In this study, to study the speciation characteristics and mobility of trace elements (As, Se, Cd, Cr, and Pb) across ultralow emission air pollution control devices, bottom ash, fly ash, gypsum, waste sludge, and wet electrostatic precipitator (WESP) slag (as combustion byproducts) as well as coal were sampled from five ultralow emission coal-fired power plants. Results indicated that most of trace elements partitioned to ash and the mobility of trace elements decreased during this process. 37.1%−99.9% of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…ESP and FF are the two main types of particulate control devices installed in coalfired power units to capture particulates from flue gas, which can influence the migration behaviors of the gaseous trace elements and remove particulate trace elements in the flue gas. Previous studies [26,29] confirmed that the synergistic removal efficiency of As, Se and Pb in flue gas by particulate control devices of ultra-low-emission units is over 90%.…”
Section: Migration Of As Se and Pb In Furnacementioning
confidence: 76%
See 3 more Smart Citations
“…ESP and FF are the two main types of particulate control devices installed in coalfired power units to capture particulates from flue gas, which can influence the migration behaviors of the gaseous trace elements and remove particulate trace elements in the flue gas. Previous studies [26,29] confirmed that the synergistic removal efficiency of As, Se and Pb in flue gas by particulate control devices of ultra-low-emission units is over 90%.…”
Section: Migration Of As Se and Pb In Furnacementioning
confidence: 76%
“…As, Se and Pb compounds connected by weak bonds in coal are oxidized and decomposed in a CFB at a combustion temperature between 800 • C and 950 • C, while As, Se and Pb compounds with high thermal stability can be decomposed and released in the PC boiler with a combustion temperature above 1300 • C. Liu et al [44] found that the volatilization ratio of As in coal was between 17% and 60% when the combustion temperature was 900 • C, and rose to 90% when the combustion temperature was up to 1500 • C. The calculation result of thermodynamic equilibrium by Contreras et al [45] indicated that Se in coal is mainly volatilized to the gas phase SeO 2 at 850 • C. Zhang et al [46] found that Pb in coal usually exists in galena and is mainly released in the form of PbCl 2 or PbS. As a result, the release of Pb can be enhanced with the decomposition of galena within the temperature range between 800 • C and 1200 • C. In addition, fly ash contains a large percentage of metal oxides, such as Fe 2 O 3 and CaO [20,21,26], providing enough absorbability to react with the As and Se existing in the flue gas to form arsenate and selenate compounds (Equations ( 1)-( 4)) [47].…”
Section: Migration Of As Se and Pb In Furnacementioning
confidence: 99%
See 2 more Smart Citations
“…The basic working principle of wet ESP includes particle charged, charged particle migration and trapping, removing the dust on the surface of collecting plate [8][9][10]. The details are as follows: (1) The high voltage electric field area in the wet ESP are full of small droplets generating from the centrifugal atomizing nozzle; (2) Then the atomizing droplets will be charged on the condition that corona discharge is produced when the electric field is added an DC high voltage.…”
Section: Experimental Principle and Equipmentmentioning
confidence: 99%